(untitled) - Hawkins, Neil (Cambridge, 2000)
The most common cause of mortality and serious morbidity due to anaesthesia is from problems with the patient's airway. The fibreoptic intubating scope gives the competent practitioner an unparalleled opportunity to secure almost any difficult airway encountered. Recent studies have also proved that it is a safe and reliable technique and it has been recommended as an important part of the armory of the modern anaesthetist. With the aid of a free CD-ROM, containing full motion video clips of some of the techniques involved and real-time views from the scope itself, Fibreoptic Intubation provides a clear and practically-orientated introduction to the equipment involved, before going on to describe the main indications for fibreoptic intubation and the variety of skills needed to make full use of the technique. A chapter on teaching the technique will be useful not only for beginners but also for their teachers. It is an essential reading for anaesthetists of all grades.
Keywords: Trachea,Khí quản; Intubation,Đặt nội khí quản